‘Can you hear me?’: communication, relationship and ethics in video-based telepsychiatric consultations - Frittgen, Eva-Maria (Journal of medical ethics, 2022)
Telepsychiatry has long been discussed as a supplement to or substitute for face-to-face therapeutic consultations. The current pandemic crisis has fueled the development in an unprecedented way. More and more psychiatric consultations are now carried out online as video-based consultations. Treatment results appear to be comparable with those of face-to-face care in terms of clinical outcome, acceptance, adherence and patient satisfaction. However, evidence on videoconferencing in a variety of different fields indicates that there are extensive changes in the communication behaviour in online conversations. We hypothesise that this might impact ethically relevant aspects of the therapeutic relationship, which plays a prominent role in psychiatry. In this paper, we review effects of video-based consultations on communication between therapists and patients in psychiatry. Based on a common understanding of video-based consultations as changing the lived experience of communication, we categorise these effects according to sensory, spatial and technical aspects. Departing from a power-based model of therapeutic relationships, we then discuss the ethical significance of this changed communication situation, based on dimensions of respect for autonomy, lucidity, fidelity, justice and humanity. We conclude that there is evidence for ethically relevant changes of the therapeutic relationship in video-based telepsychiatric consultations. These changes need to be more carefully considered in psychiatric practice and future studies.